The annotated Phantom tollbooth - Juster, Norton, 1929-2021- (Alfred A. Knopf, 2011)
Annotated edition of Norton Juster's story about ten-year-old Milo, who finds an enormous and mysterious package in his room one day-- a phantom tollbooth, with a map to a world beyond, whereupon Milo sets off on a fantastic journey, meeting the not so wicked Witch, Faintly Macabre, and the watchdog Tock, among others, and learns the importance of words and numbers. This edition includes interviews with the author and illustrator, excerpts from Juster's notes and drafts, and commentary.